(untitled) (Conference on English Language Teaching, 2023)
Extensive reading provides freedom to choose any kinds of texts that the reader want to read, both fiction and non-fiction. This research aims at investigating the students’ preference in reading non-fiction texts during extensive reading course as well as their reason. Participants of this research are 30 undergraduate students from English Education Department. There was an interview to the participants to know what kinds of non-fiction texts that they prefer to read, and why they prefer to choose them. The result showed that most of the students prefer to read news, which provides current information for them related to their real environment. Some of them also prefer to read biography, to know more about a certain figure they are curious about.